Resenha de: The Brazilian Cotton Manufacture Textille Enterprise in an Underveloped Area (1850-1950) - Luz, Nícia Villela (Revista de História, 2023)
STEIN (Stanley J.). — The Brazilian Cotton Manufacture Textile Enterprise in an Underveloped Area, 1850-1950, Harvard Universty Press, Cambridge, Massachussets, 1957, xii, 273.